Risk of kidney health among returnee Nepali migrant workers: A survey of nephrologists - Aryal, Nirmal; Sedhain, Arun; Regmi, Pramod R; KC, Radheshyam Krishna; van Teijlingen, Edwin (Asian Journal of Medical Sciences, 2021)
Background: Anecdotal reports suggest an increasing prevalence of kidney problems in returnee Nepali migrant workers from the Gulf countries and Malaysia. Aims and Objectives: This study aims to (a) explore the magnitude of the kidney health-related problems in returnee Nepali migrant workers; and, (b) assess the need for further scientific investigations. Materials and Methods: This was a self-administered survey of practicing nephrologists in Nepal. All 51 nephrologists working in Nepal (at the time of this study) were approached by email for anonymous participation using an online survey platform. Data were collected between December 2019 and February 2020. Descriptive statistics were generated for data analysis. Results: A total of 38 nephrologists completed the survey. Almost all their migrant patients were: younger than 40 years, males, from rural areas of Nepal, and had worked in Gulf countries or Malaysia. Most (92.1%) of the respondents reported that the causes behind kidney-related problems of returnee migrant workers were of unknown etiology and less likely to be linked to traditional risk factors. Chronic kidney disease and glomerulonephritis were the most common kidney health-related problems. The vast majority of respondents (76.3%) thought that the returnee migrant workers are at a higher risk of kidney-related problems than the general Nepali population. Conclusion: Nepali labor migrants in the countries of the Gulf and Malaysia could be at a higher risk of kidney health-related problems than the general Nepali population. Further rigorous scientific investigation is warranted to examine the kidney-health-related risk of Nepali migrant workers.